2021
DOI: 10.1038/s41467-021-21520-w
|View full text |Cite
|
Sign up to set email alerts
|

A CSB-PAF1C axis restores processive transcription elongation after DNA damage repair

Abstract: Bulky DNA lesions in transcribed strands block RNA polymerase II (RNAPII) elongation and induce a genome-wide transcriptional arrest. The transcription-coupled repair (TCR) pathway efficiently removes transcription-blocking DNA lesions, but how transcription is restored in the genome following DNA repair remains unresolved. Here, we find that the TCR-specific CSB protein loads the PAF1 complex (PAF1C) onto RNAPII in promoter-proximal regions in response to DNA damage. Although dispensable for TCR-mediated repa… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
32
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(36 citation statements)
references
References 62 publications
(108 reference statements)
4
32
0
Order By: Relevance
“…In contrast, EdU incorporation post-UV was not reduced in SCAI-depleted vs control cells, suggesting that the global genomic NER subpathway is not compromised in the latter (Figure 4A-B). Similarly, we found that recovery of RNA synthesis post-UV as measured by incorporation of the nucleoside analog EU (Nakazawa et al, 2010; van den Heuvel et al, 2021), an indicator of the efficiency of the transcription-coupled NER subpathway, was similar in control vs SCAI-depleted cells but clearly defective in cells in which the essential NER factor XPA was knocked-down (Figure 4C-E). Overall, the above results indicate that lack of SCAI does not cause replicative stress by compromising NER-mediated removal of UV-induced DNA lesions.…”
Section: Resultsmentioning
confidence: 53%
See 1 more Smart Citation
“…In contrast, EdU incorporation post-UV was not reduced in SCAI-depleted vs control cells, suggesting that the global genomic NER subpathway is not compromised in the latter (Figure 4A-B). Similarly, we found that recovery of RNA synthesis post-UV as measured by incorporation of the nucleoside analog EU (Nakazawa et al, 2010; van den Heuvel et al, 2021), an indicator of the efficiency of the transcription-coupled NER subpathway, was similar in control vs SCAI-depleted cells but clearly defective in cells in which the essential NER factor XPA was knocked-down (Figure 4C-E). Overall, the above results indicate that lack of SCAI does not cause replicative stress by compromising NER-mediated removal of UV-induced DNA lesions.…”
Section: Resultsmentioning
confidence: 53%
“…Indeed, defective removal of UV-induced DNA lesions is expected to exacerbate RF stalling and accumulation of RPA-ssDNA in S phase cells. To address the possibility that SCAI regulates NER efficiency, we evaluated the DNA repair synthesis step of this pathway by quantifying incorporation of the nucleoside analog EdU in G1/G2 cells post-UV (Nakazawa et al, 2010; van den Heuvel et al, 2021). As expected, siRNA-mediated depletion of the essential NER factor XPC strongly attenuated repair synthesis compared to cells transfected with non-targeting siRNA (Figure 4A-B).…”
Section: Resultsmentioning
confidence: 99%
“…NER efficiency can vary between individuals and tissue type by an order of magnitude (Tyson et al, 2009;Hubert et al, 2011). Our previous work in vivo revealed differences in CEdG among tissues of Lepr db/db diabetic mice, suggesting variability in DNA damage influenced by the local glucose environment and tissue-specific differences in NER (Jaramillo et al, 2017).…”
Section: Discussionmentioning
confidence: 93%
“…As expected, the XPC derivative showed reduced repair, an effect exacerbated by HG. Negligible luminescence was observed in CSB cells because CSB is required for transcription recovery after DNA damage ( van den Heuvel et al, 2021 ). To examine the effect of HG on CEdG repair in additional cell lines, repair assays were performed in human fibroblasts derived from a patient with mutant XPG (XP3BR-SV), a repair-competent isogenic derivative (XPG+), and MCF10A breast epithelial cells ( Fig S2C and D ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation